Irritable bowel syndrome prevalence in Latin America - Pontet, Yessica (2021)
Although irritable bowel syndrome is a common functional bowel disease worldwide, few prevalence studies have been published. Diagnosis is clinical and based on internationally agreed criteria that have changed over time. Currently the Rome IV Consensus is used as the international reference. Objective: Collect and update available prevalence data from Latin America to better understand the regional behavior of irritable bowel syndrome. Materials and methods: A search was carried out for original works, self-defined on prevalence, in the Pubmed and Lilacs databases. Presentations or posters at congresses of original works were also considered. Results: According to the established search criteria, 27 studies were found. Of these, 16 were in the general population. Two studies included the study of the prevalence of more than one population, for which reason 22 prevalence data were obtained from 9 countries. The total average prevalence for Latin America was 15.4%. The average prevalence found by the Rome II criteria was 23.5%; by Rome III 11.8% and by Rome IV 6.98%. Conclusion: This is the first review to collect data on the prevalence of irritable bowel syndrome in the general population from nine Latin countries. The average prevalence found was 15%. The variability was wide and the diagnostic criteria used made he biggest difference.